2013
DOI: 10.3233/jad-2012-121309
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cholinergic Markers and Tau Phosphorylation are Altered in Experimental Type 1 Diabetes: Normalization by Electroacupuncture

Abstract: Diabetes often correlates with tau phosphorylation and the development of Alzheimer's disease. Both are associated with brain cholinergic dysfunction that could benefit from nerve growth factor (NGF)-based therapies. Electroacupuncture (EA) improves brain NGF availability and action. Here we assessed the variations of NGF and tau phosphorylation in the cortex and hippocampus, as well as the expression of choline acetyltransferase in the basal forebrain following diabetes induction and EA in adult rats. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…Our data on experimental diabetes point to an early reduction in the mNGF/proNGF ratio in the hippocampus and cortex of diabetic rats, which is evident at 4 weeks and lasts until 8 weeks after diabetes induction. We previously demonstrated that 4 weeks after STZ treatment there was a significant reduction in neurons expressing cholinergic markers, such as the NGF receptor tyrosine kinase A (TrkA) and ChAT, in the medial septum (MS) (Rocco et al, 2013). In the present manuscript, we extended our observations to a later time-point (8 weeks), confirming the STZ-induced depletion of ChAT-expressing neurons and demonstrating a significant loss of p75 NTRexpressing cells in the MS.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our data on experimental diabetes point to an early reduction in the mNGF/proNGF ratio in the hippocampus and cortex of diabetic rats, which is evident at 4 weeks and lasts until 8 weeks after diabetes induction. We previously demonstrated that 4 weeks after STZ treatment there was a significant reduction in neurons expressing cholinergic markers, such as the NGF receptor tyrosine kinase A (TrkA) and ChAT, in the medial septum (MS) (Rocco et al, 2013). In the present manuscript, we extended our observations to a later time-point (8 weeks), confirming the STZ-induced depletion of ChAT-expressing neurons and demonstrating a significant loss of p75 NTRexpressing cells in the MS.…”
Section: Discussionsupporting
confidence: 90%
“…It has previously been shown that proNGF acts as a proapoptotic inducer, by specifically challenging the p75 NTR , in BFCN (Volosin et al, 2006). Experimental DE in rats is characterized by impaired cholinergic NGF-related features, such as the loss of septal neurons expressing ChAT and TrkA (Rocco et al, 2013) or the increase in proNGF binding to the p75 NTR -sortilin receptor complex in the hippocampus (Soligo et al, unpublished observation). Interestingly, in the present paper we found a reduction in the number of p75 NTR -positive cells after DE induction, suggesting that in pathological conditions an altered mNGF/proNGF ratio is accompanied by altered receptor expression.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations